STRENGTHENING TEACHER COMPETENCE THROUGH CONTINUOUS TRAINING IN THE ERA OF EDUCATIONAL TRANSFORMATION(LITERATURE REVIEW) - Adi Mursalin; Imelda; Aisyah (Indonesian Journal of Education (INJOE), 2025)
This study examines the role of continuous professional development (CPD) in strengthening teacher competencies in the era of educational transformation. Using a literature review approach, this study synthesises findings from recent studies, policies, and best practices to identify strategies, challenges, and opportunities in the implementation of continuous training programmes for teachers. The findings reveal that teacher competency improvement is influenced by the integration of pedagogical, professional, social, and personal skills, all of which require continuous updating in line with curriculum reforms, technology integration, and changing student needs. This study reveals the dual nature of the era of educational transformation: on the one hand, it presents challenges in the form of unequal access to training, high teacher workload, and resistance to change; on the other hand, it opens up opportunities through digital learning platforms, cross-institutional collaboration, and personalised training assisted by artificial intelligence. These findings underscore the importance of strong policy support, relevant training materials, and collaboration among stakeholders to build an inclusive, adaptive, and sustainable CPD ecosystem that can improve the overall quality of teaching and educational outcomes.